Additional procedures in cassation and supervision proceedings of civilistic procedure - L. A. Terekhova (Правоприменение, 2022)
The subject of the research is the additional powers of the Chairman of the Supreme Court of the Russian Federation in relation to cassation and supervisory complaints.The purpose of the article is to substantiate the necessity or redundancy of certain additional powers of the Chairman of the Russian Supreme Court taking into account the nature of such powers and the conditions for their application.The methodology. Analysis and synthesis, dialectical method as well as formal legal interpretation of Russian legislative acts and judicial practice of Russian Supreme Court were used.The main results. Since the transformation of the three-tier supervisory proceedings into a system of two cassation and one supervisory instance, as well as the liquidation of the Supreme Arbitration Court, the powers of the Chairman of the Supreme Court of the Russian Federation have spread to a fairly wide range of relations that allow influencing the movement of the case in the cassation and supervisory instance, and on itself initiation of a case in a supervisory instance. Moreover, such activities are far from always regulated by the norms of the law.The Chairman of the Supreme Court of the Russian Federation (or his deputy) currently has leverage over the possibility of considering a case in the cassation instance of the Supreme Court of the Russian Federation (Judicial Collegium of the Supreme Court) and in the supervisory instance (Presidium of the Supreme Court). These possibilities are called control and substitute in the article. Control powers should include: 1) regulation of key deadlines in cassation and supervisory proceedings; 2) interference in the procedure for filtering complaints. The procedure and conditions for the use of these powers are not regulated in the procedural codes. Having such powers in relation to procedural terms, the President of the Supreme Court actually influences the very possibility of initiating a case in a court of cassation or supervisory instance, as well as the duration (and, accordingly, the quality) of the examination of the complaint. The intervention of the Chairman of the Supreme Court of the Russian Federation in the procedure for filtering complaints has a clearly pronounced discretionary nature, moreover, it is selective. It would not be superfluous to point out that such as "order" in itself creates conditions for its abuse both by the participants in the case and by the courts. The substitute authority is the right of the Chairman of the Supreme Court to initiate supervisory proceedings on his own initiative, contrary to the basic rule of civil proceedings based on the principle of discretion (the case is initiated by the person whose rights have been violated). Supervisory proceedings are currently intended to appeal against judicial acts adopted by the Supreme Court of the Russian Federation itself when considering cases in the first, appeal and cassation instances. However, among the objects of appeal there are also acts of the Judicial Collegium of the Supreme Court, applications to which are possible with complaints against acts of any lower courts, with some restrictions on the decisions of justices of the peace (Article 390.4 of the Civil Procedure Code; Article 291.1 of the Arbitration Procedure Court). In this regard, the supervisory authority must continue to be viewed as the final link in the system of reviewing judicial acts. However, the system for reviewing judicial acts is very contradictory. On the one hand, there are a number of strict rules that cut off certain types of judicial acts from appeal; filtering complaints in the second cassation and supervision; establishing special rules for the jurisdiction of complaints. On the other hand, it is possible not to comply with these strict rules and directly contact the Chairman of the Supreme Court of the Russian Federation.This extraordinary power of the Chairman of the Supreme Court of the Russian Federation has been preserved, precisely because the Russian legislator firmly and consistently adheres to the conviction that it is necessary to leave at least one official who is not a party to the case the right to initiate an audit of a judicial act.Conclusions. The extraordinary powers of the Chairman of the Supreme Court are of an extra-procedural nature, at best they are based on the rules of record keeping (instead of the law), are selective and opaque.